Telemetering system and its application for fruit cultivation in greenhouses - Daohui, Zhang; Jiawei, Wang; Xiaojuan, Zong; Hairong, Wei; Dongzi, Zhu; Qingzhong, Liu (International Journal of Agricultural and Biological Engineering, 2013)
Circuit of the temperature measurement equipment was improved in order to develop temperature telemetering system for cultivating fruit facilities. The traditional temperature measuring equipments used in monitoring temperature changes in greenhouse include mercury column, merbromine column, kerosene column glass rod thermometer and mechanical inductive thermometer. Compared with the traditional method of temperature measurement the new system reduces the labor requirement and promotes precision monitoring and control of the temperature. In addition, the temperature in the greenhouse was very accurate especially at night or in rainy and snowy weather. This new temperature telemetering system will promote the development of the fruit protection cultivation.